Biological characterization and antibacterial effects of a novel virulent Acinetobacter baumannii phage strain vB_Aba_QH4 in vitro and in vivo - Ruizhe, Li; Peng, Cheng; Zian, Li; Jianwu, Zhou; Xiangren, A. (Frontiers in Microbiology, 2025)
BackgroundAcinetobacter baumannii is a major opportunistic pathogen in hospital-acquired infections, posing challenges for clinical control. This study aimed to isolate and characterize a novel strain of A. baumannii phage from hospital wastewater and to determine its biological properties and evaluate its in vitro and in vivo bacteriostatic effects.MethodsUsing A. baumannii NO.424 as the host bacterium, phages were isolated and purified using the plaques method and double-layer agar method. The host spectrum and phage microscopic morphology were determined using the plaques method and transmission electron microscopy, respectively. The Optimal multiplicity of infection, adsorption curve, one-step growth curve, thermal stability, acid–base stability, UV tolerance, and chloroform stability were determined using the double-layer agar method. Bioinformatic functional analysis was performed after genome sequencing using the Illumina platform. The in vitro and in vivo inhibitory effects were determined using the turbidimetric method and wax borer larvae animal model, respectively.ResultsA lytic phage vB_Aba_QH4 with a narrow host spectrum was successfully isolated and purified from a hospital wastewater sample using A. baumannii NO.424 as the host bacterium. vB_Aba_QH4 microscopic morphology head is positively icosahedral (60 ± 2 nm) with a retractable tail (107 ± 2 nm). vB_Aba_QH4 has an optimal MOI of 0.001, an adsorption rate of 99.99% at 6 min, an incubation period of 10 min, a cleavage period of 40 min, and a burst size of 460.5 PFU/cell. The bioactivity of vB_Aba_QH4 remained stable at 4 °C to 50 °C, and pH of 3–11. vB_Aba_QH4 was inactivated by UV light after 40 min of irradiation, and chloroform solution had no significant effect on the bioactivity of vB_Aba_QH4. Furthermore, vB_Aba_QH4 has a linear double-stranded DNA with a length of 45,017 bp and a GC content of 37.25%, with a total of 89 predicted open reading frames. vB_Aba_QH4 showed significant inhibition of A. baumannii within 12 h, with an inhibition rate exceeds 90%. The highest survival rates were 95 and 70% in the treatment and prevention groups, respectively.ConclusionvB_Aba_QH4 possesses strong environmental tolerance, rapid adsorption capacity, and good cleavage power, with in vitro and in vivo bacterial inhibition experiments showing good antimicrobial effects.